UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS V SDN 241 PALEMBANG DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN BAHASA INDONESIA - Enturia Vahdila; Effendi Nawawi; David Saputra (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to improve the learning outcomes of students in class V in Indonesian language subjects by using interactive learning media in the form of PPT slides, learning videos and word wall games. This research uses the Classroom Action Research (PTK) method with the subjects namely class V.B students at SDN 241 Palembang, totaling 27 students. Data collection techniques use observation, interviews, tests and documentation. The research results showed a significant increase in the percentage of students reaching the Minimum Completeness Criteria (KKM) from cycle 1. The average value of students was 64.07 and in cycle 2 it was 80.92. So the research results show that the use of interactive learning media can improve student learning outcomes.